2021
DOI: 10.1155/2021/8818681
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aggregate‐Forming Minerals on Thermodynamic Parameters Using Surface Free Energy Concept and Its Relationship with the Moisture Susceptibility of Asphalt Mixtures

Abstract: Moisture damage is known to be a key factor influencing the durability of asphalt pavements. This phenomenon will reduce the mechanical properties of asphalt mixtures due to its destructive effects on the adhesion of the bitumen-aggregate system and the cohesion of the bitumen membrane. The mineral properties of the aggregates of asphalt mixtures are one of the factors affecting moisture susceptibility. Therefore, the surface free energy (SFE) method, as one of the thermodynamic methods, and indirect tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For instance, Sargodha aggregate contains 4% silica content, which is the highest among all three sources ( Table 2 ). It was observed that a higher percentage of silica content causes a reduction in tensile strength of the mix since silica imparts a reduction in bond strength of the asphaltic mixture [ 45 , 46 , 47 , 48 ]. Adding SBR latex and HDPE altered the A S surface from hydrophilic to hydrophobic.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Sargodha aggregate contains 4% silica content, which is the highest among all three sources ( Table 2 ). It was observed that a higher percentage of silica content causes a reduction in tensile strength of the mix since silica imparts a reduction in bond strength of the asphaltic mixture [ 45 , 46 , 47 , 48 ]. Adding SBR latex and HDPE altered the A S surface from hydrophilic to hydrophobic.…”
Section: Resultsmentioning
confidence: 99%
“…(v) For future studies, various nanomaterials and fbers can be applied in this regard [47,48]. In addition, other failures of LEA mixtures containing CR and nanomaterials can be investigated [49,50]. Te use of electric vehicles and clean fuels can also help reduce the carbon footprint in the pavement industry [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the mechanical behavior of asphalt mixtures prepared with marble dust has proven to be technically sound and preferable to what can be achieved using fillers obtained from steel slag or granite [ 22 ]. Low percentages of SiO 2 coupled with high percentages of CaO result in a higher water resistance and reduced moisture-induced damage [ 23 ]. The possibility of achieving similar or even slightly better performance by replacing traditional fillers with waste materials and the simultaneous reduction in waste disposal problems both encouraged the present study.…”
Section: Introductionmentioning
confidence: 99%